2020
DOI: 10.1016/j.jhep.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD as a driver of chronic kidney disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) and chronic kidney disease (CKD) are worldwide public health problems, affecting up to 25-30% (NAFLD), and up to 10-15% (CKD) of the general population. Recently, it has also been established that there is a strong association between NAFLD and CKD, regardless of the presence of potential confounding diseases such as obesity, hypertension and type 2 diabetes. Since NAFLD and CKD are both common diseases that often occur alongside other metabolic conditions, such as typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
263
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(320 citation statements)
references
References 145 publications
7
263
2
8
Order By: Relevance
“…While traditionally the hepatorenal syndrome causing AKI was the main kidney-related concern in liver disease patients, more recently a link between liver steatosis, non-alcoholic fatty liver disease (NAFLD) and CKD has been emphasized [75,76]. Since NAFLD, diabetes and CKD are complications of the metabolic syndrome, this points to the potential utility of PGC-1α-based therapeutic approaches to target the different complications of metabolic syndrome.…”
Section: Liver Diseasementioning
confidence: 99%
“…While traditionally the hepatorenal syndrome causing AKI was the main kidney-related concern in liver disease patients, more recently a link between liver steatosis, non-alcoholic fatty liver disease (NAFLD) and CKD has been emphasized [75,76]. Since NAFLD, diabetes and CKD are complications of the metabolic syndrome, this points to the potential utility of PGC-1α-based therapeutic approaches to target the different complications of metabolic syndrome.…”
Section: Liver Diseasementioning
confidence: 99%
“…However, most of previous studies had a much higher prevalence of diabetes in their study samples [24,25], raising the possibility of selection bias given the strong association between diabetes and CKD. Additionally, although it is reasonable to assume that NAFLD may promote renal damage, it is still uncertain if NAFLD is associated with a speci c type of kidney disease [16]. Anyhow, despite that gouty nephropathy and diabetic kidney disease (DKD) have many risk factors in common, they are actually distinct entities with differing risk pro les.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between nonalcoholic fatty liver disease (NAFLD) and chronic kidney disease (CKD) has attracted much attention, since they share similar risk factors and pathogenic mechanisms, such as insulin resistance (IR), diabetes mellitus (DM), hyperlipidemia and obesity [12][13][14][15][16][17][18]. While numbers of previous studies indicated the presence and severity of NAFLD was a potential contributory risk factor for the development and progression of CKD, recent studies suggested no adverse association between NAFLD hepatic steatosis and renal function both in general populations and diabetic individuals [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between NAFLD and chronic kidney disease (CKD) has attracted much attention recently. NAFLD and CKD may share common pathogenic mechanisms, such as insulin resistance, type 2 diabetes mellitus, hyperlipidemia and obesity, and thus may potentially share same therapeutic targets [3][4][5]. Growing evidence suggests that patients with NAFLD have a higher risk of CKD than non-NAFLD population [6][7][8].…”
Section: Introductionmentioning
confidence: 99%